1981
DOI: 10.1128/aem.42.5.758-761.1981
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tricarboxylic acid cycle intermediates and related metabolites on the biosynthesis of aflatoxin by resting cells of Aspergillus flavus

Abstract: Resting cells of Aspergillus flavus synthesized aflatoxin from acetate as the sole carbon source after 36 h of incubation. Addition of pyruvate (5.5 mg/ml) as cosubstrate to [1-'4C]acetate and unlabeled acetate considerably reduced toxin production but increased the radioactivity on the tricarboxylic acid intermediates. This suggests that high tricarboxylic acid activity drastically affected toxin synthesis. '[he carcinogenic property of aflatoxin has stimulated many scientists to study in detail the mode of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although intensive studies of the factors affecting aflatoxin formation have been carried out in the last three decades, the mechanism that regulates aflatoxin formation remains poorly understood. The availability of readily utilizable carbohydrates, levels of certain intermediates in primary metabolism, and the cytoplasmic anabolic reduction charge ratio of NADPH to NADP are all important (24,29). More recently, most of the genes involved in the biosynthesis of aflatoxin were identified, and evidence for a complex interaction between environmental and nutritional factors and the genetic characteristics of the fungi was obtained (21).…”
Section: Discussionmentioning
confidence: 99%
“…Although intensive studies of the factors affecting aflatoxin formation have been carried out in the last three decades, the mechanism that regulates aflatoxin formation remains poorly understood. The availability of readily utilizable carbohydrates, levels of certain intermediates in primary metabolism, and the cytoplasmic anabolic reduction charge ratio of NADPH to NADP are all important (24,29). More recently, most of the genes involved in the biosynthesis of aflatoxin were identified, and evidence for a complex interaction between environmental and nutritional factors and the genetic characteristics of the fungi was obtained (21).…”
Section: Discussionmentioning
confidence: 99%
“…The tricarboxylic acid cycle plays a central role in catabolic and anabolic processes in fungi. It was pointed out that tricarboxylic acid intermediates inhibit aflatoxin production (2,20). On the other hand, Gupta et al (8) demonstrated that increased aflatoxin production was correlated with decreased activity of the tricarboxylic acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Simple sugars and acetate stimulate ( Shantha and Murthy, 1981 ), and intermediates of the tricarboxylic acid cycle inhibit the formation of AF ( Buchanan and Ayres, 1977 ; Shantha and Murthy, 1981 ). Although, at the same time, carbon sources do not regulate specifically the genes in the AF biosynthesis pathway.…”
Section: Genetics Of Aflatoxin Productionmentioning
confidence: 99%